PERBANDINGAN KEAKURATAN MODEL REGRESI MENGGUNAKAN METODE DEKOMPOSISI LU GAUSS DAN BACKWARD - Rukmono Budi Utomo (Universitas Muhammadiyah Ponorogo, 2019)
This research showing comparison accuration regression model using Gauss LU Decomposition and Backward Method. Regression model in this research is a model that explaining influence finance ratios against profit percentage in manufacture companies noted in Indonesia Stock Exchange (IDX) year 2010. The regression model is an output of Gauss LU Decomposition using SPSS and Backward method. Furthermore in this research coefficient that compile regression model is comparing between of Gauss LU Decomposition and Backward method. The result showing that coefficient of Backward Method has some errors than coefficient of Gauss LU Decomposition, but the value of nine coefficient error not bigger that 10 percent and still can be accepted. In this research also delivered accuracy of accounting profit some manufacture companies using the two of that method.